Urinary stone disease in the first year of life: is it dangerous? - ÖZEN, AHMET OĞUZHAN; ALPAY, HARİKA; GÖKCE, İBRAHİM (SPRINGER, 2013)
We have evaluated the clinical, radiological and metabolic features of infantile urolithiasis (UL). We have reviewed the medical records of 93 children who were diagnosed as having UL before 1 year of age. We recorded patient demographics, the age at diagnosis, presenting symptoms, family history, the localizations and dimensions of stones, urinary metabolic examinations, as well as physical, laboratory, and radiologic findings. Our secondary objective was to compare some features of this group with those of older children with UL followed-up in the same clinic which were previously reported. We evaluated 93 children referred to our pediatric nephrology clinics. A family history of UL was 56.2 % in the study group. Resolution of stones was observed in 30.1 % of the cases. Urinary tract infections (UTIs) were detected in 65.9 % of females and 46.2 % of males. At least one urinary metabolic abnormality was found in 79.5 % of all the children. Most commonly seen metabolic abnormality was hypercalciuria. In all patients stones were located in kidneys except one infant who had an ureteral stone together with a kidney stone. Fifteen (16.1 %) children had an accompanying systemic disorder. Among pediatric urinary stone diseases infantile UL can be regarded as a separate clinical entity. Coexistence of systemic disorders and anatomic anomalies at high frequencies may indicate a role of distinct pathogenetic mechanisms. In addition, high rates of UTIs and metabolic abnormalities in this age group justify screening for these parameters during follow-up of these children.
Keywords: Infant; Urolithiasis; Hypercalciuria; Hypocitraturia; Uricosuria; PEDIATRIC UROLITHIASIS; CHILDREN; EXPERIENCE; MANAGEMENT; CHILDHOOD; DIAGNOSIS; INFANTS; CALCIUM